2009
DOI: 10.1089/ars.2008.2150
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Blueberry Inhibits Angiogenic Tumor Growth and Enhances Survival of Mice with Endothelial Cell Neoplasm

Abstract: Endothelial cell neoplasms are the most common soft tissue tumor in infants. Subcutaneous injection of spontaneously transformed murine endothelial (EOMA) cells results in development of hemangioendothelioma (HE). We have previously shown that blueberry extract (BBE) treatment of EOMA cells in vitro prior to injection in vivo can significantly inhibit the incidence and size of developing HE. In this study, we sought to determine whether oral BBE could be effective in managing HE and to investigate the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 59 publications
(62 reference statements)
1
27
0
Order By: Relevance
“…Murine aortic endothelial (MAE) cells were maintained under the same conditions as EOMA cells, as previously described (19)(20)(21). In brief, EOMA cells (www.atcc.org) are maintained in DMEM supplemented with 10% fetal calf serum (FCS) and 1% penicillin=streptomycin, also referred to as normal growth medium (NGM), and incubated at 378C and 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Murine aortic endothelial (MAE) cells were maintained under the same conditions as EOMA cells, as previously described (19)(20)(21). In brief, EOMA cells (www.atcc.org) are maintained in DMEM supplemented with 10% fetal calf serum (FCS) and 1% penicillin=streptomycin, also referred to as normal growth medium (NGM), and incubated at 378C and 5% CO 2 .…”
Section: Cell Culturementioning
confidence: 99%
“…These conclusions are based not only on correlations observed in clinical studies, but also on experimental evidence that shows that ablation of macrophage function or infiltration into experimental tumors inhibits growth and metastases (20,31,32). By using a validated murine endothelial (EOMA) cell tumor model, we previously demonstrated that MCP-1 protein expression in EOMA cells is redox sensitive, that MCP-1 expression is required for endothelial cell (EC) tumor formation, and that antioxidant treatments directed at inhibiting MCP-1 expression in EOMA cells can decrease EC tumor incidence, size, and mortality (2,(19)(20)(21). In this work, we sought to identify the source of oxidants stimulating MCP-1 expression in EOMA cells because understanding the signaling mechanisms that result in MCP-1 expression will provide greater insight into the underlying pathologic processes that make EC tumor formation possible.…”
Section: Introductionmentioning
confidence: 99%
“…The major health benefits linked to the consumption of blueberries include a reduced risk for cardiovascular (Basu et al, 2010) and neurodegenerative (Neto, 2007) diseases. Furthermore, experiments on rodents suggest that blueberry extracts may also prevent cancer, slow tumor growth, and reverse cognitive and behavioral deficits related to stroke and aging (Lau et al, 2005;Gordillo et al, 2009).…”
mentioning
confidence: 99%
“…of the family Ericaceae. Several pharmacological activities of blueberry extracts (BBE) have been documented, including ophthalmic activity and anti-aging, anti-cancer, antibacterial, anti-angiogenesis, anti-obesity and anti-diabetic properties (Ahmet et al, 2009;Chen et al, 2010;Gordillo et al, 2009;Kolosova et al, 2004;Vuong et al, 2009). Recent studies have shown that blueberries contain anthocyanins, polyphenols and flavonoids, and appear to have the highest antioxidant capacity among the common fruits and vegetables (Ahmet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%